Manajemen Discharge Planning pada Klien dengan Demam Berdarah Dengue (DBD) - Novitasari, Fransisca Putry; K, Maria Dyah; Gasong, David Nakka; Nusawakan, Arwyn Weynand (Jurnal Kesehatan, 2019)
The role of nurses is very important, in discharge planning. Discharge planning is performed in all diseases to e the clients of the illness as well as the recovery of the patient after discharge from the hospital. One of them are patients with Dengue Hemorrhagic Fever (DHF). Discharge planning for DHF patient can be done by providing health education. Some studies find that discharge planning is in intermediate achievement because some factors such as formal education and age that affect maturity in thinking and acting. The purpose of this study is to describe the ability of nurses to perform discharge planning to a patient with DHF. This is qualitative research, the population in this study is nurses who are assigned to care DHF patient in Ambarawa Hospital. Data collected by semi-structured interview and validated by member check method. The results showed that discharge planning applied in Ambarawa Hospital was absolute discharge, and also discharge planning to DHF clients in Ambarawa Hospital was not effective yet because nurses did not know the number of dengue cases that should be reported in whole to the Health District Office. It is because the standard of success applying discharge planning depends on the reporting of DHF cases as a whole. To be concluded, delivering education must pay attention to three important aspects namely structure, culture, and technology.